The distributional consequences of supply-side reforms in general equilibrium - Konstantinos Angelopoulos; Bernardo X. Fernandez; Jim Malley (Center for Economic Studies and ifo Institute (CESifo), 2011)
Using a heterogeneous agent model allowing for different degrees of complementarity between capital, skilled and unskilled labour, this paper evaluates supply-side reforms consistent with lower public debt-to-GDP in the long-run. We find that, relative to the other tax reforms, capital tax cuts lead to the highest aggregate welfare but are skill-biased and can thus increase inequality in the long-run. Depending on the elasticity of substitution between capital and unskilled labour, falls in the capital tax can result in welfare losses for unskilled workers, even in the absence of other frictions and increases in other forms of taxation. On the other hand, reductions in labour taxes can hurt the capitalists. We also show that including the transition period in the welfare evaluation lowers the inequality effects of capital tax reduc-tions since the complementarity between capital and all labour inputs is higher in the short- than in the long-run. Finally, our results suggest that a form of irrational exuberance can arise after a tax cut under heterogeneous learning in the initial conditions after the reform.
Keywords: E25; E62; 330; tax reform; structural heterogeneity; inequality; adaptive learning; Steuerreform; Öffentliche Schulden; Einkommensverteilung; Rationale Erwartung; Wohlfahrtseffekt